CITIZENSHIP AND THE RIGHT TO HEALTH IN THE RESIDENTIAL THERAPEUTIC SERVICES - Luciane Prado Kantorski; Adriane Domingues Elesbão; Valéria Cristina Christello Coimbra; Janaina Quinzen Willrich; Cristiane Kenes Nunes; Ariane da Cruz Guedes; Valquíria de Lourdes Machado Bielemann (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928768 Aim: to assess the strategies used by the Therapeutic Residentail Service to promote the right to health and citizenship. Method: it consists of a qualitative study, of descriptive and analytical character. The study was carried out in May 2010 at a Therapeutic Residential Service in the town of Alegrete, Rio Grande do Sul. Semi-structured interviews were carried out with 12 residents, which were recorded and literally transcribed. A hermeneutical-dialectical circle was used. Results: sterategies were noticed to reach health production and citizenship: the inclusion of Therapeutic Residential Service II residents in their own houses inserted in the town of Alegrete and the administration of their own Money in cases in which autonomy is found. Conclusion: it is through acquiring houses out of Residential inserted in the society and through the financial autonomy, in some cases, that the right to citizenship and health is made possible.